2017
DOI: 10.1097/hjh.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of blood pressure in community pharmacies with ambulatory, home and general practitioner office readings

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 22 publications
0
13
0
10
Order By: Relevance
“…Plasma levels of TNF-α (19,3%; p=0,001) and IL-4 (30%; p=0,001) were increased in the control group together with 5% reduction of distance in 6 minute walk test (19 meters; p=0,001). Сердечно-сосудистые заболевания -одни из самых частых и серьезных сопутствующих заболеваний, развивающихся у больных ХОБЛ и влияющих на качество и продолжительность жизни этих пациентов [4][5][6]. По данным различных авторов, ССЗ как причина летальности больных ХОБЛ наблюдаются от 25,0 % до 48,8 % всех случаев смерти, дыхательная недостаточность -23,3 %, рак легких -20,9 % [6,7].…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Plasma levels of TNF-α (19,3%; p=0,001) and IL-4 (30%; p=0,001) were increased in the control group together with 5% reduction of distance in 6 minute walk test (19 meters; p=0,001). Сердечно-сосудистые заболевания -одни из самых частых и серьезных сопутствующих заболеваний, развивающихся у больных ХОБЛ и влияющих на качество и продолжительность жизни этих пациентов [4][5][6]. По данным различных авторов, ССЗ как причина летальности больных ХОБЛ наблюдаются от 25,0 % до 48,8 % всех случаев смерти, дыхательная недостаточность -23,3 %, рак легких -20,9 % [6,7].…”
Section: Resultsunclassified
“…В 2015 г. от онкологических заболеваний умерло 8,8 млн человек. По прогнозам ВОЗ последующие 20 лет ожидается прирост заболеваемости примерно на 70 % [5]. Однако лидирующие позиции по летальности в большинстве стран современного мира занимают сердечно-сосудистые заболевания (ССЗ).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Given that systolic pressure values correlate with higher cardiovascular risk, monitoring these values is usually the focus when deciding changes and types of antihypertensive therapy. A review article published in 2011, which compared the diagnostic accuracy of BP measured at home and at the clinic with ABPM values, demonstrated that the establishment of the final diagnosis should not rely only on values of BP measured at home and at the clinic but should also be confirmed using 24-hour ABPM 20 . In the observed group of patients, the average BP value was clearly above normal values.…”
Section: Discussionmentioning
confidence: 99%
“…• Скрининг АГ путем измерения АД в медицинском учреждении и регистрация полученных цифр АД в медицинской документации рекомендован всем пациентам с 18 лет [33,40] (табл. П1, Прил.…”
Section: принципы измерения артериального давленияunclassified